1968
DOI: 10.1111/j.1365-2494.1968.tb00577.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of an Electronic Instrument for Pasture Yield Estimation

Abstract: A model of the electronic instrument described by Campbell et al. (3) was built at the Grassland Research Institute and was found to behave in a very similar way to their New Zealand model. A considerable amount of field work was undertaken with it in 1964 and this demonstrated that no general relationship of acceptable accuracy had yet been found; nor could it be sufficiently improved by the inclusion of the meteorological and botanical factors recorded. This forces one to a consideration of double‐sampling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1970
1970
1980
1980

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…A tendency to curvilinearity for the relationship of MR with herbage parameters has been noted by some workers, e.g. Back (2), and a strong quadratic component is a feature of the relationship developed between MR and herbage yield parameters in the current work. This component was consistent over the four pasture types measured.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A tendency to curvilinearity for the relationship of MR with herbage parameters has been noted by some workers, e.g. Back (2), and a strong quadratic component is a feature of the relationship developed between MR and herbage yield parameters in the current work. This component was consistent over the four pasture types measured.…”
Section: Discussionsupporting
confidence: 73%
“…Back (2), and a strong quadratic component is a feature of the relationship developed between MR and herbage yield parameters in the current work. This component was consistent over the four pasture types measured.…”
Section: Materuls and Methodsmentioning
confidence: 93%
“…The various capacitance meters previously mentioned have been extensively field tested with mixed results. Several workers have reported promising results using these devices (Campbell et al, 1962;Alcock and Lovett, 1967;Back, 1968;Van Dyneef a/., 1968;Back et al, 1969;Johns, 1972;Currie et al, 1973;Neal and Neal, 1973) while others have found that there are too many sources of error which prohibit successful field usage of these devices in many field situations (Bryant et al, 1971).…”
Section: Capacitance Metersmentioning
confidence: 99%
“…Although high multiple correlation coefficients can occur with unacceptably high residual sums of squares (Back, 1968), we used them as summary statistics. These show relative performances of different regressor (independent) and regressand (dependent) variables, without necessarily being of use in determining whether the meter and associated regressors adequately predict a particular pasture parameter.…”
Section: (D) Statistical Analysismentioning
confidence: 99%